A Novel Technique for Bulk-Fill Resin-Based Restorations: Achieving Function and Esthetics in Posterior Teeth - Gerardo Durán Ojeda; Ismael Henríquez Gutiérrez; José Pablo Tisi; Abelardo Báez Rosales (Hindawi Limited, 2017)
Advances in the mechanical properties of composite resins have allowed for their use in posterior teeth. Conventional resins have several problems associated with polymerization shrinkage stress. The development of "bulk-fill" resins has allowed for their use in single increments up to depths of 4 mm, with very low polymerization shrinkage stress. Nevertheless, differences in anatomy and the desire for optimal esthetics present unique difficulties. This article describes a step-by-step technique using flowable bulk-fill resin as a substitute for dentin in a single increment, together with a high-reflective-index resin to restore enamel and decrease clinical time, obtaining anatomically and esthetically acceptable results without detriment to the mechanical properties required to restore the functionality of the posterior teeth.